The Homodigital Propeller Flap: A New Tool for Fingertip Reconstruction. Surgical Technique, Anatomical Study, and Clinical Relevance. Issue 2 (13th December 2021) - Roulet, Steven; Delgove, Anaïs; Chirez, Pierre; Chaput, Benoit; Casoli, Vincent; Pelissier, Philippe; Pinsolle, Vincent; Lepivert, Jean-Christophe
Abstract : Background: An ideal flap for fingertip injuries should cover a significant loss of substance and avoid joint flexion to prevent later contracture and joint stiffness. In this study, the authors describe a modified homodigital island flap—the homodigital propeller flap—to better meet these requirements. Methods: An anatomical model of fingertip loss is used to analyze the advancement achieved without flexion of the finger. Twenty-four fresh-frozen fingers were dissected. Wires were inserted to maintain joints in extension. The skin paddle was similar in location to a homodigital island flap. The neurovascular bundle was dissected without exceeding the proximal interphalangeal joint and was released from the proximal half of the paddle. Then, the homodigital propeller flap was rotated 180 degrees to cover the defect. A mixture of India ink and barium sulfate was injected into the pedicle artery after the release of the proximal half of the flap from the neurovascular pedicle to assess residual flap vascularization. India ink highlights the residual subcutaneous vascularization network of the cutaneous paddle. A radiographic study of the flap was then performed to visualize the subcutaneous vascular network of the cutaneous paddle. Results: The homodigital propeller flap achieved an average cutaneous advancement of 18 mm (range, 15 to 22 mm) and allowed full coverage of cutaneous defects for all fingers while maintaining the proximal interphalangeal joint in strict extension. Conclusions: The homodigital propeller flap is a refinement of the classic homodigital island flap. It allows efficient coverage of fingertip defects because of a large advancement without flexion of the finger, reducing the risk of stiffness.